Perlindungan Hukum Bagi Korban Pemerkosaan dalam Qanun Aceh No. 6 Tahun 2014 Tentang Hukum Jinayat di Mahkamah Syar'iyyah Kota Langsa - Azwir, Zulkarnain dan (LEGALITE, 2017)
Islam regulates legal protection for rape victims in the form of indemnity (as-shadaq) charged by the perpetrator of the dowry of mitsil. In the Criminal Code the legal protection in the form of restitution given to the victims is charged to the perpetrators who do not exceed the limits of his ability, but the country that compensates by considering the ability of the State. In Qanun Aceh No.6 regarding legal protection of victims in the form of restitution listed in Article 58 at most of 400 grams of pure gold, but in practice the mechanism of the procedure of restitution has not been sent to the Syar'iyah court of Langsa, and for compensation and rehabilitation funds, neither the State, the province nor the regions provide funding for such purposes. And for the psychological impact of the rape victim in the Syar'iyah court of Langsa the victim is traumatized, and if the victim recalls the rape she experienced, she often fainted, hit everything with her hand and dangled her head on the wall.